Highly selective isotropic gas-phase etching of SiO2 using HF and methanol at temperatures –30 °C and lower. (10th March 2023) - Hattori, T.; Kobayashi, H.; Ohtake, H.; Akinaga, K.; Kurosaki, Y.; Takei, A.; Sekiguchi, A.; Maeda, K.; Takubo, C.; Yamada, M.
Abstract: The gas-phase etching of SiO2 was examined using HF and methanol vapor at temperatures below 0 °C and at low pressure. The etching rate of SiO2 increased with decreasing temperature and showed a maximum around –30 °C. The obtained etching rate was a maximum of 40 nm min −1 at plasma-enhanced chemical vapor deposition SiO2 . The etching rate of SiN examined for comparison was more than ten times smaller than that of SiO2 under the same condition. As a result, the etching selectivity of SiO2 to SiN was found to be over 20 at –40 °C. When utilizing a low temperature of less than –30 °C, gas-phase etching of SiO2 showing a high etching rate and selectivity was achieved.